Existence and Iterative Approximation of Solutions of a System of Random Variational Inclusions with Random Fuzzy Mappings: K.R. Kazmi, F.A. Khan, Naeem Ahmad - Team, Support (Thai Journal of Mathematics, 2012)
In this paper, we introduce random P-monotone mapping and its associated proximal-point mapping in Hilbert space and discuss their some properties. Further, we consider a system of random variational inclusions with random fuzzy mappings in real Hilbert spaces. Using proximal-point mapping technique, we construct an iterative algorithm for the system of random variational inclusions. Furthermore, we prove the existence of solution of the system of random variational inclusions and discuss the convergence analysis of the iterative algorithm. The results presented in this paper generalize, improve and unify the known results of recent works [1–11].